Evaluasi Kepuasan Pengguna SIMRS dengan Metode EUCS di Rumah Sakit Citra Husada Jember - Rania Ramadhani Sofyan; Dony Setiawan Hendyca Putra; Selvia Juwita Swari; Angga Rahagiyanto (Indonesian Journal Publisher, 2024)
Citra Husada Jember Hospital has been running a hospital management information system since 2019 with the help of a third-party vendor. However, during the preliminary study, several problems were still found in the use of SIMRS, including information content that was less concise, a display that was too complicated, and errors during data processing. The purpose of this study was to evaluate hospital management information systems. Researchers used quantitative research with a sample of 109 respondents. The data analysis used is relationship analysis with the spearman rank test using the help of the SPSS program. The results showed the significance value of all variables < (α = 0.05) and was positive. The correlation coefficient value of the content variable, format variable, accuracy variable is in the medium category, ease of use variable, timeliness variable is in the strong category. All variables in the EUCS method have a significant relationship to user satisfaction. The results of this study are expected that the hospital can improve the content features of SIMRS in the future to make it easier for users.